(untitled) (Linguamática, 2025)
This paper aims to present an ongoing large-scale classification and description of Brazilian Portuguese adjectives. The 3,367 most frequent adjective lemmas in a reference corpus, corresponding to 92.09% of the occurrences of adjectives, were classified into predicative and non-predicative. The former were further classified based on argument number (one or two) and type (noun phrase or clause), which led to six different classes of predicative adjectives plus two subclasses. We also described the distributional properties of each predicative adjective: human or non-human subject and complement, clausal argument mood, copular verbs, and prepositions. The most representative class was non-predicative adjectives, followed by intransitive adjectives with noun phrase and clausal subjects, respectively. The adjectives tend to select the copulative verb ser and non-human arguments. Clausal arguments are more commonly accepted as reduced infinitive clauses or in the subjunctive mood. The most commonly accepted prepositions were para, de, and a.